Emotion diary: an artistic education process with private liberty youth in Loja / Ecuador (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article reflects on a lived experience in the Center for Adolescents in Conflict with the CAC Law, in the city of Loja, Ecuador. The article uses the language of artistic education as an opening for the development of a reflective posture about emotions and existential awareness in the theater. Drawig on the visual arts and the performing arts, a descriptive and aesthetic diary was composed, full of emotional themes explored in a progressive sense. From the painting of the self-portrait to the games and the dramatization of small contexts, the diary recorded works of artistic practice as metaphors that were meant to be explored in conversation with artists and writers who address the social responsibility of artistic education.
Keywords: Art education; Emotions; Young offenders; Theater and prison; Educacional Partner